2008
DOI: 10.1073/pnas.0711875105
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ regulates multiple proinflammatory pathways to suppress atherosclerosis

Abstract: Lipid homeostasis and inflammation are key determinants in atherogenesis, exemplified by the requirement of lipid-laden, foam cell macrophages for atherosclerotic lesion formation. Although the nuclear receptor PPAR␦ has been implicated in both systemic lipid metabolism and macrophage inflammation, its role as a therapeutic target in vascular disease is unclear. We show here that orally active PPAR␦ agonists significantly reduce atherosclerosis in apoE ؊/؊ mice. Metabolic and gene expression studies reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 54 publications
(63 reference statements)
8
156
0
Order By: Relevance
“…S3). Indeed, nuclear receptors belonging to the PPAR family have emerged as relevant in anti-inflammatory signaling mechanisms and may bind lipids (16). For example, oxidized fatty acids at concentrations in the micromolar range can activate PPARγ, which possesses an unusually large ligand-binding cavity that accommodates a wide range of molecules rather than a single ligand (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S3). Indeed, nuclear receptors belonging to the PPAR family have emerged as relevant in anti-inflammatory signaling mechanisms and may bind lipids (16). For example, oxidized fatty acids at concentrations in the micromolar range can activate PPARγ, which possesses an unusually large ligand-binding cavity that accommodates a wide range of molecules rather than a single ligand (21).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear receptors may evoke anti-inflammatory responses (16). Therefore, we sought to determine whether RvD1 interacts with specific nuclear receptors.…”
Section: Rvd1mentioning
confidence: 99%
“…This dose was chosen based on the results of the previous in vivo studies demonstrating selectivity of GW501516 as a PPARd agonist. 33,35 Investigator was not blinded as to which mouse belonged to control group and which belonged to treated group. Brain tissues were collected after mice were killed by injection of an overdose of pentobarbital (250 mg/kg body weight, i.p.).…”
Section: Materials and Methods Micementioning
confidence: 99%
“…Recently, PPAR agonists have been reported to be "exercise mimetics" and increase exercise endurance without exercise in mice, suggesting a unique therapeutic approach for life-style-related disease 113) . PPAR also regulates multiple pro-inflammatory pathways to suppress atherosclerosis 114) , and plays some roles in angiogenesis with endothelial progenitor cells 115) . Recent investigations have revealed that PPAR is intimately involved in metabolic regulation and atherosclerosis.…”
Section: Pparmentioning
confidence: 99%